2018
DOI: 10.5539/ijel.v8n4p192
|View full text |Cite
|
Sign up to set email alerts
|

A Semiotic Analysis of Gender Discursive Patterns in Pakistani Television Commercials

Abstract: The study is multidisciplinary that ventures into the domains of semiotics, linguistics and cultural studies. Media has become one of the most viable social institutions of disseminating information to a wider audience. It has got power to (re)frame the ideology of larger audience through its visual/linguistic content and to pave the way to social change. The current study aims to investigate the manifestation of gender discursive patterns in the Pakistani television commercials. This study draws its theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Electronic media advertising influences people's buying behavior, attitudes, and lifestyles. The importance of advertising cannot be overlooked as it is the most readily available source of spreading information, knowledge, and entertainment (Nasir, 2018). Media content, text, and images represent socio-cultural values and strengthen the belief system of a convoluted society.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Electronic media advertising influences people's buying behavior, attitudes, and lifestyles. The importance of advertising cannot be overlooked as it is the most readily available source of spreading information, knowledge, and entertainment (Nasir, 2018). Media content, text, and images represent socio-cultural values and strengthen the belief system of a convoluted society.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Iftikhar, Aziz, and Latif (2011) found that an advertisement is considered successful if it reveals the identity of gender and exposes female models to change customers' purchase intentions against the religious values of Islam. Media content becomes a hindrance by portraying stereotypic gender roles, glorification of women, false representation of oppressed society, and unfair malpractices to represent the negative image of societal values (Nasir, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the field of semiotics, Nasir (2018) carried out a study in which he investigated gender discursive patterns in TV commercials in Pakistan. He aimed to highlight the representation of gender-binary relations that existed in Pakistani TV commercials.…”
Section: Semiotic Studies On Advertisementsmentioning
confidence: 99%